Role of gut microbiota in neuroinflammation: a focus on perioperative neurocognitive disorders - Zhou, Qun; Chen, Tuo; Wang, Xiaoying; Xu, Zhongnan; Song, Yue; Liu, Shan; Ge, Yali; Gao, Ju (Frontiers in Cellular and Infection Microbiology, 2025)
Perioperative neurocognitive disorders (PND), including postoperative delirium, preoperatively cognitive impairment, postoperative cognitive dysfunction, and delayed neurocognitive recovery, represent common complications following anesthesia and surgery, especially in the elderly. As the global population ages, PND is receiving increasing attention due to its prolonged the hospitalization, reduced quality of life and elevated mortality rate. A growing body of evidence has been suggested that the gut-brain axis, a communication system between the gut microbiota and the neuroinflammation, plays a critical role in the development and progression of cognitive impairment. Perioperative interventions, including anesthesia, surgical stress, result in gut microbiota dysbiosis and subsequently trigger neuroinflammation. Therefore, it is necessary to clarify the underlying mechanistic associations between the gut microbiota and the neuroinflammation during PND progression. In this review, we synthesize current knowledge on the mechanistic interplay between gut microbiota dysbiosis and neuroinflammation in PND pathogenesis, which provide reasonable and novel therapeutic approaches targeting the gut-brain axis for PND.